1995
DOI: 10.1164/ajrccm.151.5.7735616
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical ventilation-induced pulmonary edema. Interaction with previous lung alterations.

Abstract: The risk of lung injury due to alveolar overdistension during mechanical ventilation has been clearly delineated in healthy animals with intact lungs. In contrast, the effect of high-volume ventilation (HV) on previously injured lungs is less well documented: whether HV would simply add its own deleterious effects or act synergistically with previous injury has not been addressed. We compared the effect of 7 ml/kg body weight tidal volume mechanical ventilation for 2 min with that of 25 (HV25), 33(HV33), and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
78
0
8

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(89 citation statements)
references
References 28 publications
3
78
0
8
Order By: Relevance
“…[7][8][9][10] Mechanical ventilation strategies associated with high VT and high airway pressure can produce microvascular injury in the lungs, leading to pulmonary edema, which results in lymphatic flow acceleration that allows bacteria to enter systemic circulation. [13,14] Deterioration of mucociliary activity caused by mechanical ventilation can also facilitate passage of bacteria by disrupting bacterial clearance. The bacteria may be forced to spread out of the airway due to the physical impact of positive pressure, which is reported to be more significant in small animals.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] Mechanical ventilation strategies associated with high VT and high airway pressure can produce microvascular injury in the lungs, leading to pulmonary edema, which results in lymphatic flow acceleration that allows bacteria to enter systemic circulation. [13,14] Deterioration of mucociliary activity caused by mechanical ventilation can also facilitate passage of bacteria by disrupting bacterial clearance. The bacteria may be forced to spread out of the airway due to the physical impact of positive pressure, which is reported to be more significant in small animals.…”
Section: Discussionmentioning
confidence: 99%
“…These procedures are restricted by the risks of oxygen toxicity and barotrauma. [31][32][33] In this context, the prone position could enable the use of lower fractions of inhaled oxygen and lower airway pressures. Moreover, lung inflation is more homogeneous in PP, contributing towards reduction in the risks of ventilator-induced lung injury.…”
Section: Discussionmentioning
confidence: 99%
“…Alguns estudos demonstraram a ocorrência de lesão pulmonar por distensão mecânica do parênquima normalmente inflado. Como a ventilação corrente é distribuída ao parênquima pulmonar inflado, quanto maior o volume de pulmão colapsado, maior o volume corrente que irá penetrar nas regiões não-colapsadas, promovendo hiperinsuflação sustentada nessas regiões e possivelmente volutrauma/barotrauma e inflamação com suas conseqüências deletérias ao tecido pulmonar 45,49,50 . O efeito nocivo de volumes correntes relativamente aumentados distribuídos para o parênquima pulmonar não-colapsado está estabelecido em pacientes com lesão pulmonar aguda 51,52 e pode ser também verdadeiro em pacientes submetidos à anestesia geral prolongada, em que o colapso dos pulmões acontece e pode determinar aumento das complicações respiratórias pós-operatórias.…”
Section: Conseqüências Clínicas Das Atelectasias Intra-operatórias Naunclassified
“…Some studies have demonstrated the presence of pulmonary lesion caused by the mechanical distension of normally inflated parenchyma. Since the tidal volume is distributed to the inflated pulmonary parenchyma, the tidal volume that will be distributed to non-collapsed regions of the lungs increases proportionally to the volume of collapsed lung, leading to sustained hyperinflation of those regions and possible volumetric trauma/barotrauma and inflammation, with their deleterious consequences to the lung tissue 45,49,50 . The noxious effects of relatively increased tidal volume distributed to non-collapsed pulmonary parenchyma has been established in patients with acute lung lesions 51,52 and the same might be true for patients undergoing prolonged general anesthesia who develop collapse of certain areas of the lungs, therefore increasing the incidence of postoperative respiratory complications.…”
Section: Clinical Consequences Of Intraoperative Atelectasis In Patiementioning
confidence: 99%